Optimizing management practices in mulberry for intensive fodder production in humid tropics of Kerala - Raj, A.K.; Kunhamu, T.K.; Kiroshima, S. (Indian Journal of Agroforestry, 2020)
Mulberry (Morus indica L.), a prominent agroforestry tree species and the sole feed of silkworms, is also a potential animal fodder as a supplement to poor quality roughages, but management practices that ensure both quantity and suitable quality as cattle feed and sustainable production are to be standardized under humid tropical conditions of Kerala. The study was conducted to determine the optimum tree density, stem pruning height and pruning interval of mulberry to obtain maximum fodder yield and quality. The treatments included combinations of three levels of tree density viz., 27,777 plants ha-1 (60 cm x 60 cm spacing), 22,222 plants ha-1 (75 cm x 60 cm spacing) and 17,777 plants ha-1 (75 cm x 75 cm spacing), two pruning heights (0.5 m and 1.0 m from ground level) and three pruning intervals of 8 weeks, 12 weeks and 16 weeks, laid out in 3 x 2 x 3 factorial randomized block design replicated thrice. The results indicated that tree density and pruning interval showed prominent influence on forage and protein yields, where as pruning height mainly affected the longevity and health of trees. Annual fodder biomass and protein yield was greater for the higher density stands. Increasing the pruning interval up to 12 weeks increased the dry matter, foliage and nutrient yields significantly and thereafter declined at 16 weeks. Even though higher leaf-stem ratio was observed at shorter interval of 8 weeks, total annual foliage yield was higher at 12 weeks pruning interval. Higher dry matter and nutrient yields were obtained from taller stocks pruned at 1m height. Therefore, In humid tropical conditions with annual rainfall of 210-300 cm, mulberry should be planted at 60 cm x 60 cm spacing (27,777 trees ha-1), pruned at 1.0 m height above the ground level and at an interval of 12 weeks to achieve greater and sustainable dry matter (36.70 tons/hectare/year, 2nd year) and nutrient yields and palatable fodder with 70 percent foliage content. By proper planning of harvesting schedules, the 12 weeks pruning interval can also ensure availability of fodder during dry season. Establishment and proper management of mulberry plantations thus offers a cheap source of quality forage to Kerala farmers against the highly expensive concentrate feeds.